2019
DOI: 10.1155/2019/1092415
|View full text |Cite
|
Sign up to set email alerts
|

From “Every Day” Hormonal to Oxidative Stress Biomarkers in Blood and Follicular Fluid, to Embryo Quality and Pregnancy Success?

Abstract: Background Oxidative stress appears to be involved in oocyte growth and maturation that when impaired results in poor embryo quality and lower potential to implant. The biochemical microenvironment of the oocyte (follicular fluid (FF)) consists of hormones and other various substances regulating the balance between oxidants and antioxidants. Aim The aim of this study was to examine the possible impact of selected biomarkers (“every day,” hormonal biomarkers, enzymatic and nonenzymatic antioxidants, and also ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
(41 reference statements)
2
4
0
Order By: Relevance
“…Logistic regression analysis revealed that the antioxidant activity of follicular fluid is a good predictor of oocyte fertilization and top-quality embryos. Both TOSC vs. peroxyl radicals and TOSC vs. hydroxyl radicals demonstrated high sensitivity and specificity, accordingly to previous published data [ 29 ]. Similarly, IL-10 displayed a good predictive ability for fertilization and embryo quality, thus revealing the importance of maintaining an oocyte microenvironment with a specific anti-inflammatory status.…”
Section: Discussionsupporting
confidence: 88%
“…Logistic regression analysis revealed that the antioxidant activity of follicular fluid is a good predictor of oocyte fertilization and top-quality embryos. Both TOSC vs. peroxyl radicals and TOSC vs. hydroxyl radicals demonstrated high sensitivity and specificity, accordingly to previous published data [ 29 ]. Similarly, IL-10 displayed a good predictive ability for fertilization and embryo quality, thus revealing the importance of maintaining an oocyte microenvironment with a specific anti-inflammatory status.…”
Section: Discussionsupporting
confidence: 88%
“…Our study confirmed that the ovarian GCs and FF of patients with repeated COS (placebo group) did show higher levels of 8-OHdG. Moreover, high levels of SOD and GSH-Px activity were related to the success rate of IVF 42 , 43 , which suggested that poor clinical pregnancy outcomes and mitochondrial function damage were associated with the imbalance of oxidation and antioxidation caused by repeated COS. However, administration of BSTJF in our study significantly decreased the levels of 8-OHdG but increased the Mn-SOD and GSH-Px levels compared to the placebo group, indicating that BSTJF can improve mitochondrial function and clinical pregnancy outcomes by adjusting the oxidation-antioxidation balance.…”
Section: Discussionsupporting
confidence: 81%
“…When assessing hydrogen peroxide in FF of the sibling follicles, the highest concentrations are observed from follicles following poor embryo quality, and the lowest concentrations are found in empty follicles [ 34 ]. Women with idiopathic infertility and greater GPx activity are related to high embryo quality [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nitrate overproduction is attributed to women who did not achieve pregnancy [ 36 ]. Women who achieved pregnancy presented lower ROS, MDA, protein carbonyls, GR, SOD, and GST and higher TAC, GPX, and tocopherol [ 24 , 35 , 37 41 ]. Thus, enhanced lipid and protein oxidation are present among women with an unfavourable outcome.…”
Section: Resultsmentioning
confidence: 99%